2011
DOI: 10.1111/j.1750-3841.2011.02359.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Immature and Mature Green Coffees by Attenuated Total Reflectance and Diffuse Reflectance Fourier Transform Infrared Spectroscopy

Abstract: The objective of this work was to evaluate the potential of Fourier transform infrared spectroscopy (FTIR) in the characterization and discrimination between immature and mature or ripe coffee beans. Arabica coffee beans were submitted to FTIR analysis by reflectance readings employing attenuated total reflectance (ATR) and diffuse reflectance (DR) accessories. The obtained spectra were similar, but in general higher absorbance values were observed for nondefective beans in comparison to immature ones. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Such bands have been previously reported present in spectra of roasted Arabica and Robusta coffee samples (Craig et al, 2012b;Kemsley et al, 1995) and also of crude coffee samples (Craig et al, 2011(Craig et al, , 2012a. Paradkar and Irudayaraj (2002) also reported two sharp peaks at 2882 and 2829 cm À1 in samples of caffeinated beverages such as coffee, tea and soft drinks.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Such bands have been previously reported present in spectra of roasted Arabica and Robusta coffee samples (Craig et al, 2012b;Kemsley et al, 1995) and also of crude coffee samples (Craig et al, 2011(Craig et al, , 2012a. Paradkar and Irudayaraj (2002) also reported two sharp peaks at 2882 and 2829 cm À1 in samples of caffeinated beverages such as coffee, tea and soft drinks.…”
Section: Resultsmentioning
confidence: 70%
“…In general, DRIFTS provided spectra that presented higher intensity of absorption in comparison to ATR-FTIR. Both techniques were satisfactory for discrimination between immature and mature coffees (Craig et al, 2011). However, even though DRIFTS provided complete discrimination between defective (low quality) and non-defective (high quality) coffees, ATR-FTIR could not provide complete discrimination between nondefective and sour (fermented) coffees (Craig et al, 2012a).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These beans represent about 20% of the total coffee produced in Brazil and similar amounts can be expected in other producing areas around the world (Mendonça, Franca, Oliveira, & Nunes, 2008;Ramalakshmi, Kubra, & Rao, 2007). Although separated from the non-defective beans prior to commercialization in external markets, the majority of the defective beans are dumped in the Brazilian internal market and, overall, a low-grade roasted coffee is consumed in the country (Craig, Franca, & Oliveira, 2011). The negative effect that such beans have on coffee quality can be associated to specific problems that occur during harvesting and post-harvest processing operations.…”
Section: Introductionmentioning
confidence: 95%
“…Research interest on defective and low quality coffee beans has intensified over the past years, given the increasing awareness regarding the negative aspects they impart to the quality of the roasted and ground coffee used for beverage preparation and consumption (Craig et al, 2011;Craig, Franca, & Oliveira, 2012;Farah, Monteiro, Calado, Franca, & Trugo, 2006;Franca, Oliveira, Mendonça, & Silva, 2005;Mancha Agresti, Franca, Oliveira, & Augusti, 2008;Mendonça et al, 2008;Mendonça, Franca, Oliveira, & Afonso, 2009;Oliveira, Franca, Mendonça, & Barros-Junior, 2006;Ramalakshmi et al, 2007;Vasconcelos, Franca, Glória, & Mendonça, 2007). Such studies have shown that there are physical and chemical differences between defective and non-defective coffee beans prior to roasting, but only a few have attained some success regarding discrimination of defective and non-defective coffees after roasting.…”
Section: Introductionmentioning
confidence: 99%